2017
DOI: 10.1016/j.chemosphere.2017.03.119
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation in major ion chemistry and source identification of secondary inorganic aerosols in Northern Zhejiang Province, China

Abstract: To investigate the seasonal and spatial variations of ion chemistry of fine particles in Northern Zhejiang Province (NZP), China, one year-long field sampling was conducted at four representative sites (two urban, one suburb, and one rural sites) in both cities of Hangzhou and Ningbo from December 2014 to November 2015. Twelve water soluble inorganic ions (WSII) were characterized in this comprehensive study. The annual average of PM concentration in NZP as overall was 66.2 ± 37.7 μg m, and urban sites in NZP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 77 publications
6
32
2
2
Order By: Relevance
“…Cl − is considered to be an important ion contributing to the formation of PM 2.5 in coastal cities (Xu et al, 2017). Cl − showed the high concentration in this study, which may be attributed to both sea source and anthropogenic emission.…”
Section: The Major Water Soluble Ions Analysismentioning
confidence: 55%
See 2 more Smart Citations
“…Cl − is considered to be an important ion contributing to the formation of PM 2.5 in coastal cities (Xu et al, 2017). Cl − showed the high concentration in this study, which may be attributed to both sea source and anthropogenic emission.…”
Section: The Major Water Soluble Ions Analysismentioning
confidence: 55%
“…Factor 4 had a significant contribution of Cl − , accounting for 7.6% of PM 2.5 . In addition to marine source (seawater), coal combustion and chlor-alkli chemical industry could be identified as the main source for Clin this study (Xu et al, 2017;Liu et al, 2017).…”
Section: Source Apportionmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al selected four representative locations (two cities, one suburb site and one rural site) in Hangzhou and Ningbo from December 2014 to November 2015 in order to study the seasonal and spatial variation in terms of fine particle pollution in Zhejiang Province. With help of the Principal Component Analysis (PCA) method, they found that industrial emissions, biomass burning, and formation of secondary inorganic aerosols are the major sources of fine particles in Zhejiang Province [28]. Fu et al studied the potential correlation between conjunctivitis and air pollution based on the air pollutant data from the Environmental Protection Department of Zhejiang Province from 1 July 2014 to 30 June 2016 and data of 9737 outpatient visits for conjunctivitis at the Eye Center of the Second Affiliated Hospital of Zhejiang University School of Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…(1) By constructing the six major pollutants defined by China's air quality standards, we have evaluated the air quality of Zhejiang Province more comprehensively than the existing research. In similar studies of air quality in Zhejiang Province, scholars often use particulate pollutants as research objects [27,28,78]. Then, few research works contain the six major pollutants.…”
mentioning
confidence: 99%